Smoking cessation advice and non‐pharmacological support in a national sample of Aboriginal and Torres Strait Islander smokers and ex‐smokers. (1st June 2015) - Thomas, David P; Bennet, Pele T; Briggs, Viki L; Couzos, Sophia; Hunt, Jennifer M; Panaretto, Kathryn S; Stevens, Matthew; Borland, Ron
Abstract: Objectives: To describe recall among a national sample of Aboriginal and Torres Strait Islander smokers and recent ex‐smokers of having received advice to quit smoking and referral to non‐pharmacological cessation support from health professionals, and their association with quit attempts. Design, setting and participants: The Talking About The Smokes project used a quota sampling design to recruit 1721 smokers and ex‐smokers who had quit ≤ 12 months previously from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Strait. Baseline surveys were conducted from April 2012 to October 2013. Results for daily smokers were compared with 1412 Australian daily smokers surveyed by the International Tobacco Control Policy Evaluation Project between 2006 and 2011. Main outcome measures: Participants' recall of having been: seen by a health professional in the past year, asked if they smoke, advised to quit, and referred to other cessation support services; and having made a quit attempt in the past year. Results: Compared with other Australian daily smokers, higher proportions of Aboriginal and Torres Strait Islander daily smokers saw a health professional in the past year (76% v 68.1%) and were advised to quit smoking (75% v 56.2% of those seen). Most Aboriginal and Torres Strait daily smokers who saw a health professional recalled being asked if they smoke (93%). Aboriginal and Torres Strait Islander daily smokers who had been advised to quit were more likely to have made a quit attempt in the past year than those who had not (odds ratio, 2.00; 95% CI, 1.58–2.52). Among all Aboriginal and Torres Strait Islander smokers and recent ex‐smokers who had been advised to quit, 49% were given a pamphlet or brochure on how to quit, but fewer were referred to the telephone Quitline (28%), a quit‐smoking website (27%) or a local quit course, group or clinic (16%). Conclusion: Most Aboriginal and Torres Strait Islander daily smokers recalled being recently advised by a health professional to quit, which was associated with making a quit attempt.